Rule based clinical decision support system for hematological disorder - Chen, Y.Y. (2013)
Evidence Based Medicine (EBM) has become a popular approach to medical decision making. It is a method of assisting in clinical decision making by using the most relevant research evidence to answer clinical questions. Complete Blood Count (CBC) is one of the most commonly ordered blood test that could be done within minutes and is mostly used as a basis for further testing. Therefore, CBC could be used as a base to quickly diagnose a patient and later on, use external clinical evidence from systematic research to further diagnose the patient. This paper proposes the development of a clinical decision support system (CDSS) to assist physicians in evidence based practice. The system will be able to provide the list of external evidence (electronic medical journals) for each type of generated probable disease. Usability and user acceptance testing were conducted with a group of physicians and medical students. This study reveals some usability issues of the system and significant improvements that are required to improve the accuracy of the system in generating probable hematological disorder. Â© 2013 IEEE.